2004
DOI: 10.1159/000081728
|View full text |Cite
|
Sign up to set email alerts
|

Serum Antibodies to Retinal Antigens in Lung Cancer and Sarcoidosis

Abstract: Objective: Autoantibodies to various neuronal proteins frequently accompany lung cancer and their appearance may precede cancer symptoms. In this study we examined which retinal antigens (RAs) are recognized by sera of patients with lung cancer and whether the occurrence of serum antibodies to particular RAs is characteristic for cancer in comparison with a noncancer lung disease. Methods: Sera of 72 patients with non-small-cell lung cancer (NSCLC), 29 with small-cell lung cancer (SCLC), 27 with sarcoidosis (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…However, autoantibodies immunoreactive to these antigens are rarely reported in cancer patients but associated with some inflammatory or metabolic diseases (34,35), implicating that tumor antigen-mediated immunosuppression may occur in tumor malignancy. Consistent with previous studies to detect CML28 (36) and ENO1 (14) autoantibodies in chronic myelogenous leukemia and lung patients, respectively, our data obtained from Western blotting analyses also show that only a small percentage (7.4%) of the cancer patients, including patient CA926, develop high titer of antibodies against ENO1. The same conclusion is also observed when a sandwich ELISA to quantify levels of the autoantibodies was used, showing that the levels in the cancer patients are significantly lower (P < 0.01) than those in effusion fluids of the non-tumor-associated patients and in sera of healthy control subjects (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, autoantibodies immunoreactive to these antigens are rarely reported in cancer patients but associated with some inflammatory or metabolic diseases (34,35), implicating that tumor antigen-mediated immunosuppression may occur in tumor malignancy. Consistent with previous studies to detect CML28 (36) and ENO1 (14) autoantibodies in chronic myelogenous leukemia and lung patients, respectively, our data obtained from Western blotting analyses also show that only a small percentage (7.4%) of the cancer patients, including patient CA926, develop high titer of antibodies against ENO1. The same conclusion is also observed when a sandwich ELISA to quantify levels of the autoantibodies was used, showing that the levels in the cancer patients are significantly lower (P < 0.01) than those in effusion fluids of the non-tumor-associated patients and in sera of healthy control subjects (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 92%
“…One study identified ENO1 as antigenic target on human oral cancer cells that was recognized by autologous CD4 + T cells (13). Immunoreactive sera to ENO1 were also recently found in 6.9% to 13.8% of patients with different subtypes of lung cancer (14,15), suggesting that it can be an immunogenic target in cancer patients.…”
mentioning
confidence: 99%
“…The x-axis shows the molecular weight (kDa) and the y-axis the density of the antigen-antibody-reactivity (U) against the retinal antigens sue [27]. Anti-retinal antibodies can also be found in other diseases like small-cell cancer of the lung, [28,29] retinitis pigmentosa, [30,31] and paraneoplastic retinopathy [11]. It is still not know, if these antibodies are an epiphenomenon or if they are causative for AMD.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been considered that although anti-recoverin Abs may be the primary cause of CAR, other autoantibodies may also be then involved in the pathological process [16]. In the sera of carcinoma patients, Abs to various retinal proteins have been detected [3,5,13]. The occurrence of anti-a-enolase Abs in the sera of patients with CAR was first described by Adamus et al [10].…”
Section: Discussionmentioning
confidence: 99%
“…Neurological examination, including mental status, was unremarkable except for the absence of Achilles tendon reflexes. The patient's serum was subjected to immunoblot analysis using retinal extract and purified retinal antigens [12,13]. The serum did not react with purified recoverin, retinal arrestin, or guanylate cyclase-activating proteins (GCAPs) and also did not show any reactivity with these antigens in retinal extract.…”
Section: Case Reportmentioning
confidence: 99%